Solusi sehat di lahan sempit: edukasi penanaman TOGA mandiri di perkotaan - Ananto, Agus Dwi; Muliasari, Handa; Deccati, Rizqa Fersiyana (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
Tanaman Obat Keluarga (TOGA) are a valuable local resource that can be cultivated as an alternative approach to maintaining family health independently. However, public knowledge and practical skills related to the types of TOGA and proper cultivation techniques remain limited. This community service program aimed to improve community awareness and skills in cultivating TOGA within household environments. The program was implemented through socialization activities using educational pamphlets, instructional videos, and interactive door-to-door discussions across three target areas: urban settlements, rural villages, and residential complexes. The results demonstrated a significant improvement in participants' knowledge of TOGA varieties. Before the program, only about 40% of participants were familiar with more than five types of TOGA, which increased to 85% after the socialization activities. Furthermore, over 75% of participants could correctly describe the basic steps of TOGA cultivation, and approximately 60% of households had already begun planting TOGA in their yards or using simple containers such as pots and polybags. Evaluation also revealed strong enthusiasm and active involvement, as evidenced by participants' engagement in discussions and their initiative to form small groups for continuous TOGA development. In conclusion, this community service activity successfully enhanced participants' knowledge, skills, and motivation to cultivate TOGA. The program is expected to contribute to long-term community self-reliance in herbal-based health maintenance and foster the establishment of sustainable TOGA communities within local neighborhoods.